Constraints on Precipitation of the Ferrous Arsenite Solid H7Fe4(AsO3)5. Issue 3 (1st May 2014) - Masue‐Slowey, Yoko; Slowey, Aaron J.; Michel, F. Marc; Webb, Samuel M.; Fendorf, Scott
Abstract : Formation of Fe(II)‐As(III) solids is suspected to limit dissolved As concentrations in anaerobic environments. Iron(II) precipitates enriched in As(III) have been observed after microbial reduction of As(V)‐loaded lepidocrocite (γ‐FeOOH) and symplesite (Fe(II)3 (As(V)O4 )2 ]·8H2 O) and upon abiotic reaction of Fe(II) with As(III). However, the conditions favorable for Fe(II)‐As(III) precipitation and the long‐term stability (relative to dissolution) of this phase are unknown. Here we examine the composition, local structure, and solubility of an Fe(II)‐As(III) precipitate to determine environments where such a solid may form and persist. We reveal that the Fe(II)‐As(III) precipitate has a composition of H7 Fe4 (AsO3 )5 and a log K so of 34 for the dissolution reaction defined as: H7 Fe4 (AsO3 )5 + 8H + = 4Fe 2+ + 5H3 AsO3 . Extended X‐ray absorption fine structure spectroscopic analysis of H7 Fe4 (AsO3 )5 shows that the molecular environment of Fe is dominated by edge‐sharing octahedra within an Fe(OH)2 sheet and that As is dominated by corner‐sharing As III O3 pyramids, which are consistent with previously published structures of As(III)‐rich Fe(II) solids. The H7 Fe4 (AsO3 )5 solid has a pH‐dependent solubility and requires millimolar concentrations of dissolved Fe(II) and As(III) to precipitate at pH <7.5. By contrast, alkaline conditions are more conducive to formation of H7 Fe4 (AsO3 )5 ; however, a high concentration of Fe(II) is required, which is unusual under alkaline conditions.